Deskripsi Dampak Pembelajaran Daring Terhadap Orang Tua dan Siswa Sekolah Dasar di RT 10 dan RT 25 Kelurahan Dusun Besar Kota Bengkulu - Agustini Elni Putri; Edi Ansyah; Hengki Satrisno (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
This study aims to find out about the impact of online learning on parents in economic, social and psychological aspects in RT 10 and RT 25 Kelurahan Dusun Besar Bengkulu City, as well as to determine the impact of online learning on elementary school children in economic, social and psychological aspects in RT 10 and RT 25 Kelurahan Dusun Besar. This research is qualitative research. The subjects in this research are impact and online learning. Data collection was taken through interviews, observation, documentation. The author acts as a direct interviewer to collect data through parents and elementary school children in the neighborhood of RT 10 and RT 25. The results of the study indicate that the impact of online learning on parents has undergone many changes, including from an economic perspective where they are constrained by the cost of internet quotas which are increasing day by day. In addition, from a social point of view, there have also been changes such as difficulties i n implementing an online learning system for children and children's habits that must be supervised. As well as the impact of online learning on elementary school children, they have difficulty in following and understanding the online learning system because most of them are new to online learning since COVID-19 and no one teaches in detail about the method and process of learning. They better understand the face-to-face learning process than the online learning system. Parents and elementary school students also experience boredom because this online learning system has been implemented for too long.